Pengaruh Aplikasi Elisitor Nuswantara Biosaka Terhadap Pertumbuhan Tanaman Bayam (Amaranthus Tricolor) Sebagai Sumber Belajar Biologi di SMA - Siti Wardania Malawat; Ratna Prabawati; Sutardi Sutardi (STKIP HARAPAN BIMA, 2026)
The objective of this research is to determine the influence of the application of the nuswantara biosaka elicitor on the growth of spinach plant (Amaranthus tricolor). This research was conducted by comparing 4 treatment groups with varying biosaka doses, starting from group P0 (control), P1(5 ml), P2 (10 ml), and P3(15 ml). The type and design is an experiment using a Completely Randomized Design (CRD), carried out from August to September 2025, at Jl.S. Mambramo, Matalamagi Village, North Sorong, Sorong City. The samples used were 4 polybags of spinach plants per treatment, the data analysis technique used descriptive statistic, followed by One-Way ANOVA test and Tukey test at the 5% level. The results of the research show that the administration of the nuswantara biosaka elicitor has a significant effect on increasing plant height and stem diameter, with the results owned by biosaka with a dose of 10 ml (P2), where as the administration of biosaka has no significant effect on the number of leaves and fresh weight of spinach plants, but biosaka with a dose of 10 mil still gives the heighest results with a comparison that is not large enough compared to other treatments. Likewise with the root length parameter where the best results are owned by treatment without biosaka or control.